Судакский районный уполномоченный народного управления религиозными делами мусульман Крыма в 1920–е годы Билял Фаикъ - Хайруддинова, Э.М. (Культура народов Причерноморья, 2013)
Статтю присвячено вивченню життєдіяльності Біляла Файкъа, районного уповноваженого
Народного управління релігійними справами мусульман Криму Судакського району в 1920–і роки. Білял
Файкъа не був звичайним районним уповноваженим, він займав активну позицію в управлінні, брав
участь у підготовці і проведені з'їздів мусульман, у виданні журналу «Асрій мусульманлик'»: підготував і
опублікував 11 статей. У даній публікації розкривається зміст основних його робіт, які переважно
стосувалися питань релігійної освіти та просвіти. The origin and development of Islam in Ukraine is an important objective of national historical
science. Of course, the most important region in the state where Islam has historically developed was Crimea.
In today's multi–ethnic Crimea Islam is the second denomination of the number of people who practice this
religion. For many centuries there has accumulated valuable experience of living together representatives of
many ethnic groups. In this sense, the Crimea is a unique society in which there and solved the problems
associated with multi–ethnic regions, including in the field of interfaith relations. Difficult period in the history
of Islam in the peninsula is the period of Soviet power.
Therefore, for studying the history of Islam in the Crimea should be explored the vital activity of Bilal Faik,
Sudak's district commissioner of Muslims management religious institute in the 1924–1928 years. Bilal Faik was
not an ordinary district commissioner, he has active role in management, participated in the publication of the
magazine "Asriy musulmanlyk": prepared and published 11 articles. This publication reveals the contents of his
main works, which are mainly related to issues of religious education and enlightenment. He urged the Muslims
of Crimea to reform the system of religious education and active participation in the life of modern society. Статья посвящена изучению жизнедеятельности Биляла Фаикъа, районного
уполномоченного Народного управления религиозными делами мусульман Крыма Судакского района в
1920–е годы. Билял Фаикъ не был обычным районным уполномоченным, он занимал активную позицию в
управлении, участвовал в подготовке и проведении Всекрымских мусульманских съездов, в издании
журнала «Асрий мусульманлыкъ»: подготовил и опубликовал 11 статей. В данной публикации
раскрывается содержание основных его работ, которые преимущественно касались вопросов
религиозного образования и просвещения.